The young adult service: An evaluation of a youth mental health service in the independent sector in Ireland. Issue 5 (3rd November 2020) - Bond, Laura; Power, Paddy
Abstract: Aims: Increasing concerns about the specific needs and rates of mental illness among young adults have spurred the development of youth mental health services. Yet few outcome studies exist. This study aims to evaluate a young adult service in an independent mental health sector in Ireland. Methods: This is a service evaluation using a retrospective, descriptive and naturalistic study design. Routine demographic, diagnostic and service usage data were collected at entry into the service. Outcomes were recorded at discharge from the service using the Clinical Global Impression (CGI) improvement scores. Factors associated with better or worse outcomes were analyzed. Results: Five hundred and sixty‐seven young adults were assessed and managed during a 3‐year period by the Young Adult Service. Their characteristics fell midway between adolescent and adult mental health service populations. They had high levels of Axis I & II co‐morbidities reflecting the complex and fluid nature of emerging conditions in this age group. The majority (62.8%) had clinically improved by the end of follow‐up. Outcomes were significantly better in those who were hospitalized, prescribed psychotropic medication, received 1:1 psychology sessions and attended a group‐based psychology program or group program for specific disorders. One hundred and sixty‐six patients (29.3%) dropped out of follow‐up. Drop out was associated with longer time spent in the service, being treated solely in the community, without medication, not having a developmental disorder and not transferring from CAMHS. Conclusions: This study demonstrates that it is possible to establish an effective youth mental health service with favourable outcomes within a broader mental health system. It provides a benchmark for similar services, bridging the gap between adolescent and adult mental health services.